Novice and Professional Interpreters' Material and Mental Process: An SFL-Based Study - Putu Desi Anggerina Hikmaharyanti; Ida Ayu Made Puspani; Ni Wayan Sukarini; Ni Luh Ketut Mas Indrawati (Leksema: Jurnal Bahasa dan Sastra, 2026)
The exploration of Systemic Functional Linguistics (SFL) application particularly the ideational metafunction in spoken text like simultaneous interpreting within a reflective narrative text of legal and security context, focusing on the realization of mental and material processes has been limited to access. This study compares interpreting performance of 3 novices and 3 professional interpreters as they interpret an audio recording from Indonesian to English discussing border issues to investigate the realization of mental and material processes. Through qualitative descriptive approach of the interpreted texts, the study examines how each group constructs experiential meaning, especially in rendering cognitive (mental) and action-oriented (material) processes. Results indicate that novice and professional interpreters used material and mental processes in similar proportions, yet the quality of their realizations varied, with professionals demonstrating more accurate and consistent rendering. Novice interpreters, however, tend to generalize or omit key elements, particularly in complex mental processes, leading to reduced accuracy in meaning transfer. These differences highlight the impact of interpreter experience on the quality of simultaneous interpreting in border reflective narrative contexts containing speaker’s reflection and experience. The findings underscore the value of SFL as an analytical framework in interpreter training and assessment, especially in enhancing sensitivity to ideational meaning within reflective narrative texts.